APLIKASI BRIKET CAMPURAN ARANG SERBUK GERGAJI DAN TEPUNG DARAH SAPI PADA BUDIDAYA JAGUNG MANIS (Zea mays saccharata Sturt.) DI TANAH PASIR PANTAI - Septia Handayani (FP AGRO 16 UMY 011, 2016)
The research is Application Briquette of Sawdust Charcoal and Cow Blood Flour On Sweet Corn (Zea mays saccharata Sturt.) Cultivation in the Sand Beach has done in Green House and Land Experiment Faculty of Agriculture, University of Muhammadiyah Yogyakarta in November 2015 until March 2016. The purpose of this research is to obtain composition briquettes mixture of the charcoal sawdust and cow flour blood to supply a part of nitrogen and also to increase the growth and yield of sweet corn in land sand beach. This study used an experimental method which arranged in completely randomized design (CRD) with the design of single factor treatment consisted of 4 treatments. as follows: treatment P0: Without Briquette (Manure + Urea + SP36 + KCl), treatment P1: 99% Charcoal Sawdust + 1% Cow Flour Blood + 3.439 gram of Urea + SP36 + KCl, Treatment P2: 98% Charcoal Sawdust + 2% Cow Flour Blood + 2.396 gram of Urea + SP36 + KCl, treatment P3: 97% Charcoal Sawdust + 3% Cow Flour Blood + 1.354 gram of Urea + SP36 + KCl. Each treatment was repeated 3 times so that there are 12 experimental units consisting of three plant samples that contained 36 plants. Observation parameters which is plant height, leaf number, root length, fresh weight of plants, plant dry weight, fresh weight of root, root dry weight, cob length, diameter cobs and cobs fresh weight. The result showed that all treatments briquettes positive effect on all parameters except the observation of the root length. Treatment tends to be better is Briquette composition P2 (98% Charcoal Sawdust + 2% Cow Flour Blood + 2,396 gram Urea) who is able to substitute the use of urea by 70% with the result that the average sweet corn cobs 113.06 gram. Keywords: Sweet Corn, Sand Beach, Briquette of Charcoal Sawdust and Cow Flour Blood